2022
DOI: 10.1108/apjba-10-2020-0379
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of learning organization on proactive work behavior: mediating role of employee resilience

Abstract: PurposeThe paper examines the role of learning organization in enhancing employees’ proactive work behavior. Furthermore, drawing on the conjectures of broaden-and-build and conservation of resources theory, this study tested the mediating role of employee resilience on the relationship between learning organization and proactive work behavior.Design/methodology/approachThe data for this study were collected over two measurement periods (six months apart) via a structured questionnaire among Indian IT/ITES (In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…This finding is similar to previous studies. Some researchers reported a series of management policies that could enhance resilience at work, such as tailored training programs [ 8 ], moderate-to-vigorous physical activity [ 9 ], learning organizational culture [ 24 ], etc. Yet, these studies are piecemeal based.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is similar to previous studies. Some researchers reported a series of management policies that could enhance resilience at work, such as tailored training programs [ 8 ], moderate-to-vigorous physical activity [ 9 ], learning organizational culture [ 24 ], etc. Yet, these studies are piecemeal based.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that resilience at work partially mediated the influences of HPWS on thriving at work and job burnout, yet, in different directions. In a nurse-focused study, although the literature has reported that resilience at work can enhance positive employee outcomes [ 22 , 23 , 24 ] and reduce negative employee outcomes [ 21 , 23 ], there has been no research to explore and test whether HPWS can impact employee outcomes through developing resilience at work. Our research filled this gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that organizations cannot survive and meet the competitive advantage without learning and with the earliest knowledge of their workforce (Alipour & Karimi, 2011;Siddique, 2018). LO develop learning strategies and promote learning through their systematic working environment, leading to positive outcomes, i.e., OI, proactive behaviors and successful implementation of CSR (Adam, Indradewa, & Syah, 2020;Malik, 2022;Osagie et al, 2022). Scholars explained that positive policies and practices and training approaches for learning of employees enables them to transform their values, behaviors and norms which resultantly produces positive things, i.e., sustainability and profitability (Law, Hills, & Hau, 2017), and innovation.…”
Section: Innovationsmentioning
confidence: 99%
“…More recently, authors have advocated that learning organisations contribute to change efficacy and the contextual performance of their employees (Budhiraja, 2021). Studies also acclaim that learning organisations support their employees to learn new skills and deal with constant changes at the workplace, which in turn makes employees more secure to try new ideas and exhibit proactive work behaviour (Malik, 2023), leading to enhanced levels of employee satisfaction, commitment, and engagement (Hendri, 2019). Lastly, learning culture supports and facilitates interaction and dialogue, which leads to uncovering mistakes and improving individual performance.…”
Section: Introductionmentioning
confidence: 99%